2022
DOI: 10.1007/s11682-022-00698-7
|View full text |Cite
|
Sign up to set email alerts
|

Semantic fluency deficits and associated brain activity in Parkinson’s disease with mild cognitive impairment

Abstract: People living with Parkinson’s disease (PD) with poor verbal fluency have an increased risk of developing dementia. This study examines the neural mechanisms underpinning semantic fluency deficits in patients with PD with mild cognitive impairment (PD-MCI) compared to those without MCI (PD-NC) and control participants without PD (non-PD). Thirty-seven (37) participants with PD completed a cognitive assessment battery to identify MCI (13 PD-MCI). Twenty sex- and age-matched non-PD patients also participated. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…In the PD literature, Mak et al (2015) found increased right fusiform gyrus activity during an fMRI facial perception task compared to HCs, potentially compensating for left hemispheric dysfunction (Cardoso et al, 2010). Our previous work also revealed increased right angular gyrus activity in people with PD-MCI compared to HCs and cognitively intact people with PD during an alternating category fluency task, indicating additional recruitment of the contralateral hemisphere in PD with cognitive impairment (Yang et al, 2022). While increased activity in the right hemisphere during category fluency has been reported with respect to normal ageing (Meinzer et al, 2009), the aforementioned studies highlight PD-specific compensatory activity over and above that of age-matched controls.…”
Section: Contralateral Compensatory Mechanisms In Pdmentioning
confidence: 65%
“…In the PD literature, Mak et al (2015) found increased right fusiform gyrus activity during an fMRI facial perception task compared to HCs, potentially compensating for left hemispheric dysfunction (Cardoso et al, 2010). Our previous work also revealed increased right angular gyrus activity in people with PD-MCI compared to HCs and cognitively intact people with PD during an alternating category fluency task, indicating additional recruitment of the contralateral hemisphere in PD with cognitive impairment (Yang et al, 2022). While increased activity in the right hemisphere during category fluency has been reported with respect to normal ageing (Meinzer et al, 2009), the aforementioned studies highlight PD-specific compensatory activity over and above that of age-matched controls.…”
Section: Contralateral Compensatory Mechanisms In Pdmentioning
confidence: 65%
“…Semantic disfluency is a common problem in progressive supranuclear palsy (PSP) and Parkinson's disease (PD). Patients with PSP or PD tended to generate fewer correct words than age-matched healthy adults in the semantic fluency test [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, they have proven valuable in identifying cognitive deficits associated with neurological and psychiatric disorders, monitoring disease progression, and evaluating the effectiveness of relevant interventions (e.g., da Silva et al 2004). Alterations in verbal fluency performance have been observed in conditions such as aphasia, schizophrenia, epilepsy, Alzheimer's, or Parkinson's disease in adults (Bose et al 2022;Carpenter et al 2021;Chrobak et al 2022;Robert et al 1998;Tallberg et al 2010;Yang et al 2022), and attention deficit hyperactivity disorder (ADHD), Down syndrome, autism spectrum disorder (ASD), developmental language disorder (DLD), or dyslexia in children (e.g., Begeer et al 2013;Koren et al 2005;Mengisidou et al 2020;Raboutet et al 2010;Ralli et al 2021;Troyer et al 1997).…”
Section: Introductionmentioning
confidence: 99%